ANALISIS PENGARUH INDEKS PEMBANGUNAN MANUSIA, PDRB PER KAPITA, DAN JUMLAH PENGANGGURAN TERHADAP JUMLAH PENDUDUK MISKIN DI PROVINSI JAMBI - Yunie Rahayu (Ekonomis: Journal of Economics and Business, 2018)
Poverty is a problem faced by all countries in the world, especially the developing countries, such as Indonesia. Poverty is a complex issue that is affected by a variety of interrelated factors, such as people's income levels, unemployment, health, education, access to goods and services, geographic location, gender, and location the environment. The number of poor population in Central Java is relatively lebihtinggi compared to laindi province of Indonesia, that is occupying ranked second in the number of poor population the largest in Indonesia after East Java. This research aims to analyze how and how much the variable influences the human development index, GDP per capita, and the number of poor population against unemployment in Jambi province in the year 2016. Methods of analysis in this study using multiple linear regression analysis with the method of Ordinary Least Square (OLS) that use data between spaces (cross section) district/town in Jambi province year 2016 with the help of software Eviews 4.1. The results of this research indicate that the variable is the human development index (HDI) a negative and significant effect against the poor population in the province of Jambi, the per capita GDP is negative and significant effect against the number of poor population in The province of Jambi, the unemployment and the number of positive and significant effect against the poor population in the province of Jambi.Keywords: population of the poor, the human development index (HDI), GDP per capita, and the number of Unemployed